Oscillatoria salina Biswas – a new species for Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Oscillatoria salina Biswas (Cyanophyceae, Oscillatoriaceae) is recorded for the first time for Ukraine. The new finding is described and illustrated.
Keywords: cyanoprokaryotes, Oscillatoria salina, halophytes, Azov seashore, Ukraine.